Disiplin Kinerja Pegawai Negeri Sipil di Masa Pandemi COVID-19 di Tinjau dari Peraturan Pemerintah RI No. 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil - Hamdani Padli; Irfan Harmain; Muhammad Al Faraby; Yunita Ellianda (Universitas Medan Area, 2023)
Employment Discipline of Jambi BPSDM Civil Servants during the Covid-19 period According to PP No. 94 of 2021, namely there are still employees who do not comply with disciplinary rules regarding working hours after joint leave. this is influenced by the condition of Covid 19, so there are civil servants who are constrained to return or return to Jambi. covid-19 In connection with the enactment of Government Regulation of the Republic of Indonesia Number 94 of 2021 concerning Disciplinary Actions for Jambi BPSDM Employees so far, namely socialization to all employees. then civil servants to comply with obligations by working in a WFH manner and the leadership provides sanctions for violations of disciplinary prohibitions. in accordance with PP Number 94 of 2021, through the application of work discipline to BPSDM Jambi-19 employees during the Covid-19 period, namely through socialization of disciplinary rules to employees and leaders who supervise their implementation, and in Jambi Disciplinary actions carried out by officers within the BPSDM environmentthe state is subject to disciplinary action with the category of light, moderate, or severe disciplinary action every year, especially on religious holidays.